Training and Assistance in the Implementation of Disaster Safe Schools/Madrasahs (SMAB) as an Effort to Reduce Disaster Risk in Muhammadiyah 1 High School Malang City - Yana S. Hijri; Wahyudi Kurniawan; Saiman Saiman (CV. Rayyan Dwi Bharata, 2023)
Until now, schools in Indonesia that have received disaster education, whether facilitated or only limited to socialization, are still recorded at around 9%, which is still very few. SMA Muhammadiyah (SMAM) 1 Malang City, one of the schools in a potential disaster area, is located in a watershed area (DAS), a one-way road that has a risk of disaster, such as traffic accidents, landslides, and fires. Meanwhile, the vulnerabilities include building maps which tend to be difficult for the evacuation process in the event of a disaster. In 2018 and 2019 every rainy season there are always schools affected by landslides at the back of the school which is right in the Brantas DAS caused by the erosion of the river banks. Training and Assistance in the Implementation of Disaster Safe Schools/Madrasahs (SMAB) as an Effort to Reduce Disaster Risk at Muhammadiyah 1 Middle School Malang City based on Law no. 24 of 2007 concerning Disaster Management. It clearly states that everyone has the right to receive education, training, counselling, and skills in disaster management, both in situations where a disaster does not occur or when there is a potential for disaster. Through education it is hoped that disaster risk reduction efforts can achieve broader targets and can be introduced earlier to all students, by integrating disaster risk reduction education into the school curriculum as well as into extracurricular activities. Preparation for the implementation of disaster-safe schools/madrasas (SMAB) begins with compiling materials on the SMAB framework and transformation of implementation information based on guidelines from BNPB/BPBD and the Ministry of Education and Culture/Disdikbud. The second step is to arrange training for educators and education staff regarding the framework and assistance for SMAB implementation. The last stage is compiling disaster risk reduction learning practices for students in subjects and compiling activities to increase students' knowledge and skills about first aid, protection and rescue.